A new deep-bodied species of Antigonia (Teleostei, Antigoniidae) from the Andaman Sea (northeastern Indian Ocean) - Prokofiev, Artem M.; Psomadakis, Peter N.; Gon, Ofer (Zootaxa, 2020)
A new species of boarfish, Antigonia emanuela, is described from two specimens collected in the Andaman Sea off the coast of Myanmar during bottom trawl surveys conducted by the R/V Dr Fridtjof Nansen in 2015 and 2018. It is unique within the genus in the combination of the deeply rhomboid body (1.1–1.2 times deeper than long), nine dorsal-fin spines, premaxilla strongly bent in middle, scales with deep apical crest armed with numerous spinules, soft dorsal, anal and caudal fins bright-yellow in life. Two other Antigonia species captured during these surveys are A. indica and A. ovalis, the latter species being a first report for the Andaman Sea.